(untitled) (Huellas, 2026)
The objective of this work is to analyze the spatial distribution of the educational level of the population of the Metropolitan Region of Buenos Aires (RMBA) in 2022. The methodological procedures carried out include the creation of educational indicators from census variables, the application of linkage analysis to determine its relational structure between levels, cartographic representation in spatial modeling and its relationship with the social map. The application is based on quantitative spatial analysis and presents a geographical synthesis of the study area with a surface area of ​​14,018 km2 and 16,480,574 inhabitants.